INVESTIGATION OF THE DYNAMIC LOAD OF THE JOINT-PLATFORM OF THE JOINT TYPE FROM ROUND PIPES LOADED BY TANKER CONTAINERS (Transport systems and technologies, 2021)
The dynamic loading of the load-bearing structure of the articulated platform car made of round pipes loaded with tank containers was determined. The research was conducted by mathematical modeling. The solution of the equations of motion is carried out in the MathCad software package. It is established that under the influence of a longitudinal force of 2.5 MN on the front stops of the autocoupling, the acceleration on the first section of the platform car is 27.7 m/s² from the side of the force application, and on the second - 24.4 m/s2.To reduce the dynamic load of the load-bearing structure of the platform car, the possibility of using the concept of a harness device on it as an alternative to a typical self-coupling device is considered. The quenching of the kinetic energy of the impact is carried out due to the viscous resistance forces arising in the concept.The proposed implementation allows to reduce the dynamic load of the load-bearing structure of the platform car by 10% compared to the use of a standard self-coupling device.The conducted researches will promote creation of innovative designs of cars-platforms and increase of efficiency of use of railway transport.
Keywords: transport mechanics, platform car, load-bearing structure, dynamic loading, harness device concept.